2019
DOI: 10.5195/jyd.2019.717
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Youths’ Educational Aspirations in the Somali Diaspora

Abstract: This article shares findings from a 10-month qualitative longitudinal study that offer insight into the educational aspirations of American youth (grades 6-9) who belong to the Minnesota Somali diaspora and highlight the social and cultural influences that shape these aspirations. The findings show that while the majority of youth participants (at one point in the study) expressed that they wanted to become doctors in the future, these aspirations were informed by family values around helping others in Somalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The results showed that PFE had a significant effect on AFE-WE and concern, control, curiosity, and confidence, supporting Hypotheses 1 and 2. Consistent with the current findings, the existing literature underlined the relationships between optimism and adolescent future expectations (e.g., Iovu et al, 2018;Tzenis, 2019) as well as between positive beliefs about the future and work and education-related variables such as success, motivation, and career planning (e.g., King & Gaerlan, 2014). In addition, considering that optimism refers to positive outlook and orientation toward future (Carver et al, 1994), the current results were consisted with the previous work indicated its significant relations with career adaptability (e.g., Buyukgoze-Kavas, 2014;Santilli et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results showed that PFE had a significant effect on AFE-WE and concern, control, curiosity, and confidence, supporting Hypotheses 1 and 2. Consistent with the current findings, the existing literature underlined the relationships between optimism and adolescent future expectations (e.g., Iovu et al, 2018;Tzenis, 2019) as well as between positive beliefs about the future and work and education-related variables such as success, motivation, and career planning (e.g., King & Gaerlan, 2014). In addition, considering that optimism refers to positive outlook and orientation toward future (Carver et al, 1994), the current results were consisted with the previous work indicated its significant relations with career adaptability (e.g., Buyukgoze-Kavas, 2014;Santilli et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, considering very competitive education system which requires to pass a centralized university entrance exam, unemployment rates (TurkStat, 2021a), and depression among high school students, especially among those who prepare university entrance exam in Turkey (e.g., Yildirim et al, 2007), adolescents might have thought that their expectations of future exceed their control. Third, it was reported that curiosity, which is related with self and environmental exploration, hence attached to being inquisitive (Savickas, 2005) might cause negative feelings or beliefs about the future when adolescents have low levels of hope (Tzenis, 2019). Similarly, the previous research indicated that curiosity was positively related with career decision-making difficulties of adolescents due to the lack of readiness (Karacan-Ozdemir, 2019), implying that when adolescents had higher level of inquisitives for the future or explored their options more they felt not ready for the future, which resulted in higher level of career decision-making difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Young people explained that their background and faith were both central to their identity, as they guided their behaviour in various contexts and instructed them on how to be a good person. Young people in this study attributed their good behaviours to their faith and culture (Tzenis 2018). They expressed that the rules and teachings of their faith and cultural traditions manifested in behaviours that made them better students, family members, and morally sound people.…”
Section: Islamophobiamentioning
confidence: 80%
“…Youth in the Somali diaspora often find themselves resisting negative Western perceptions and stereotypes of their identities. A study conducted by Joanna Tzenis (2018) discussed the ways in which Somali youth in a Minnesota school enacted their agency by decidedly keeping and claiming their faith and culture in the face of systems who belittled it (Tzenis 2018). In this study Somali youth identified as both Somali and Muslim; they felt that these two parts of their identities were important parts of who they were.…”
Section: Islamophobiamentioning
confidence: 89%
“…Appadurai [ 31 ] conceptualises aspiration as a cultural capacity, constructed ‘in the thick of social life’ and embedded with family-mediated values that shape people’s imaginations for the future. This understanding draws attention to the reality that some have more opportunities to exercise their capacity to explore pathways to their imagined futures—in part because of the unequal distribution of social and cultural capital [ 32 34 ] links this directly to the diaspora experience. Drawing on the work of Bhabha [ 35 ] and others, Kardaszewicz [ 36 ] similarly emphasises the importance of understanding a ‘good education’ as part of the diaspora identity, expressed as ‘the daily engagement with the local environment and in the actual experience of pursuing educational aspirations’.…”
Section: Discussionmentioning
confidence: 99%